A Course of Pure Mathematics : Third Edition - Hardy, G. H. (Godfrey Harold), 1877-1947 (Salt Lake City, UT : Project Gutenberg, 2012)
"A Course of Pure Mathematics" by G. H. Hardy is a textbook published in 1908. It introduces mathematical analysis and calculus, organizing topics from real variables and complex numbers through derivatives, integrals, and infinite series. Aimed at top-tier students, it helped reform mathematics teaching in the UK and Cambridge. The book features challenging problems in number theory analysis and includes a distinctive approach to defining angles through integral calculus. It remains influential after ten editions and continues as a popular resource for pure mathematics. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Course_of_Pure_Mathematics
Release date is 2012-02-05
Keywords: Functions; Calculus